Impact of Science on African ariculture and food Security - Anandajayasekeram, P (CABI, 2014)
The book is organized into three major parts. Part I addresses challenges and contributions in African agricultural development, and presents available evidence to demonstrate the impact of R&D investment and discusses the role of science and technology in the transformation of African agriculture. Part II, Results of Impact Assessment in Eastern and Southern Africa, is a collection of impact study results from the region. These case studies deal with a wide range of enterprises including food crops, cash crops, livestock, floriculture and forestry products. Part III provides an overview of methodologies and best practices for conducting similar studies. The contents of the book emanate from individual and collaborative research by the authors through various research programmes over the past decades. This book addresses African agricultural development problems, and it is aimed at researchers, policy makers, policy advisors and donors. It can be used as a primary or complementary textbook in postgraduate courses in agricultural development, agricultural economics, research management, crop science and agronomy. It will also be valuable for planners and donors interested in African agricultural development.